Inter-rater and intra-rater reliability of a clinical protocol for measuring turnout in collegiate dancers. (2nd January 2019) - Greene, Amanda; Lasner, Andrea; Deu, Rajwinder; Oliphant, Seth; Johnson, Kenneth
ABSTRACT: Reliable methods of measuring turnout in dancers and comparing active turnout (used in class) with functional (uncompensated) turnout are needed. Authors have suggested measurement techniques but there is no clinically useful, easily reproducible technique with established inter-rater and intra-rater reliability. We adapted a technique based on previous research, which is easily reproducible. We hypothesized excellent inter-rater and intra-rater reliability between experienced physical therapists (PTs) and a briefly trained faculty member from a university's department of dance. Thirty-two participants were recruited from the same dance department. Dancers' active and functional turnout was measured by each rater. We found that our technique for measuring active and functional turnout has excellent inter-rater and intra-rater reliability when performed by two experienced PTs and by one briefly trained university-level dance faculty member. For active turnout, inter-rater reliability was 0.78 among all raters and 0.82 among only the PT raters; intra-rater reliability was 0.82 among all raters and 0.85 among only the PT raters. For functional turnout, inter-rater reliability was 0.86 among all raters and 0.88 among only the PT raters; intra-rater reliability was 0.87 among all raters and 0.88 among only the PT raters. The measurement technique described provides a standardized protocol with excellent inter-rater and intra-rater reliability when performed by experienced PTs or by a briefly trained university-level dance faculty member.